2019
DOI: 10.1103/physrevfluids.4.123902
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of airfoil noise near stall conditions

Abstract: This is the accepted version of the paper. This version of the publication may differ from the final published version. Permanent repository link: https://openaccess.city.ac.uk/id/eprint/23398/ Link to published version: http://dx.Abstract The[AU: Please check edited affiliations for accuracy][AU: Please check edited title; 'airfoil' is the US spelling. Is 'Investigation of the' necessary in the title? Often titles omit wording such as that since it's understood.]main focus of this paper is on investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
6
27
0
Order By: Relevance
“…Once the vortex reaches the TE a dipole pulse is emitted, seen clearly on the aerofoil pressure side by the expansion wave travelling upstream in frames (ii)-(vi). These results confirm the experimental observations made by Lacagnina et al [8], who suggested that a possible stall noise mechanism could be convection and scattering of wall pressure at the TE generated by nearby shear layer instabilities. The shear layer vortices are strongest from around the mid-chord location to the TE.…”
Section: Noise Source Mechanismssupporting
confidence: 92%
See 2 more Smart Citations
“…Once the vortex reaches the TE a dipole pulse is emitted, seen clearly on the aerofoil pressure side by the expansion wave travelling upstream in frames (ii)-(vi). These results confirm the experimental observations made by Lacagnina et al [8], who suggested that a possible stall noise mechanism could be convection and scattering of wall pressure at the TE generated by nearby shear layer instabilities. The shear layer vortices are strongest from around the mid-chord location to the TE.…”
Section: Noise Source Mechanismssupporting
confidence: 92%
“…The most prominent observation in the literature is that the stall is characterised by a high level of low frequency sound [2][3][4][5][6][7][8][9]. More specifically, in the light stall regime increased low frequency broadband levels are observed, while in deep stall low frequency tones are also exhibited [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TE serrations) developed for TE noise may be less effective under separated flow conditions. Three possible mechanisms for the noise generation have been suggested in a recent paper by Lacagnina et al 6 for near stall conditions. They theorize that shear layer instabilities, flapping, and shear layer coherent shedding could be a source of unsteady pressure on the wall, which convects towards, and is scattered by the TE.…”
Section: Introductionmentioning
confidence: 96%
“…Stall noise has been documented by experimental studies [1][2][3][4][5][6][7] , where the key emerging feature is a high level of low frequency sound. Various airfoil profiles have been tested by Moreau et al 3 at Reynolds number Re ∞ = 150, 000 and for Mach numbers M ∞ < 0.1.…”
Section: Introductionmentioning
confidence: 99%